Description of how the Prophet Muhammad SAW dressed in Metaverse using Virtual Reality (VR) and Augmented Reality (AR) Technology - Miswan Surip,; Mohamad Zulluqman Afiq Rahmat,; Muhamad ‘Irfan ‘Adlie Zainudin,; Said Amirul Hasloni, (Multidisciplinary Applied Research and Innovation, 2022)
: There are many Muslims that practice the wearing of trendy fashion clothes that do not follow the way of our Prophet. This statement is true since we can see male and female, especially teenagers and youth wearing fashionable clothing that does not follow the Islamic law, especially photos that are posted in social media. The lack of exposure can be seen throughout the decades where people in the mosque frequently asked questions regarding manner in dressing according to Islamic Law. The project is intended to develop a visual guidance on how Prophet Muhammad SAW wear his clothing through Metaverse using Virtual Reality and Augmented Reality as an application for android operating system platform, for Muslims in the range of 4 years old and above as they start to understand and learn. It helps them to enhance and improve their knowledge about the visual of how Prophet Muhammad SAW wears clothing. For the character’s model and environment’ model are created using Blender and Unity software and the procedures are based on ADDIE methodology.